STRATEGY FOR MAINTAINING THE QUALITY OF CATCHES BY IMPLEMENTING QUOTA AND ZONE BASED FISHING IN ZONE 3 - Syaifullah, Tornanda; Saptono, Ari; Purwana, Dedi; Hamidah, Hamidah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
The quality of catches is determined by how the best fishing practices are conducted. A program or policy is needed to support the achievement of high-quality catches. Ministry of Marine Affairs and Fisheries implements quota and zone-based fishing, one of the objectives of this policy is to have catches with high quality.  This study aims to develop strategies to maintain the quality of catches at Ports in Zone 3 where fishing vessels are required to land their catches at ports within the same zone. The methodology in this research is the Soft System Methodology (SSM) approach with CATWOE analysis. The study identifies various issues related to fish handling on vessels, fish handling facilities and infrastructure, as well as fish distribution and processing, all of which impact the quality of the catch. The results find that improving product quality is closely linked to onboard fish handling practices, fish processing units, and the development of fish industries. This relationship is described by the eigenvector, with downstream industry strengthening scoring 0.438, quota and zone-based fishing management scoring 0.348, and human resource capacity scoring 0.248. Based on these findings, strengthening downstream industries is crucial to supporting the quality of catches within the quota and zone-based fishing. This is further evidenced by laboratory test results showing that distribution from Tual Fishing Port to Karangsong Fishing Port a 28.57% decline in organoleptic tests, a 92.31% increase in Escherichia coli, and a 40% increase in Total Plate Count (TPC). The study also highlights the fishermen's proficiency, skills, and expertise in handling fish catches and implementing cold chain systems up to the consumer level, which significantly influence the quality of fish catches. To realize these findings, it is recommended to provide training for fishermen, supply cooling facilities and vessels, and develop cold chain systems up to the consumer level. This study shows that the zoning system will help maintain fish quality. Additionally, strengthening supporting infrastructure is essential to improve fish quality in the capture fisheries sector.